Positive Psychology and SLA Revisited: Unearthing Positive Emotions in EFL Classrooms - Oladrostam, Elnaz; Rezaee, Abbas Ali; Nushi, Musa (Frontiers in Psychology, 2022)
Positive psychology focuses on the constructive effects of positive emotions on human behavior. Considering the recent plethoric research on positive emotions and SLA, this study pursues two important aims. The first aim is to find out whether there is any significant disparity between EFL teachers’ and learners’ views on an inventory of positive psychology in language learning (IPPLL) which was fostered by researchers. The second goal is to find out whether teachers’ practices conform to their views on IPPLL and those expressed in the interview which was conducted with them. To this end, a 54-item questionnaire was developed and the revised questionnaire was administered to 385 learners. The results indicated that the teachers, in comparison with the learners, scored higher on all categories of the IPPLL. Moreover, unlike what they had expressed on the questionnaire and in the interview, the teachers did not capitalize on positive emotions as evinced in both teachers’ practice and learners’ experience with learning English. Implications of the findings for teacher education courses are presented.